EVALUASI TEKNIS KEHILANGAN AIR MINUM DI PERUMDAM KOTA MAGELANG: STUDI KASUS PADA DISTRICT METERED AREA (DMA) PERUM KORPRI - Pratama, Ekadhana Chana; Nurhayati, Ervin; Hastuti, Dian Suci (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2025)
The high level of non-revenue water (NRW) poses a significant challenge in managing the water supply system of Perumdam Kota Magelang, especially in the Perum Korpri District Metered Area (DMA), which recorded a 56.16% loss from a total annual input volume of 171,770 m³. This study aims to evaluate the technical aspects of water loss and formulate NRW reduction strategies based on Internet of Things (IoT) technology. The methods include the collection of primary and secondary data, water balance analysis using WB-Easy Calc, and hydraulic network simulation through EPANET 2.2. The evaluation focuses on network pressure, consumption fluctuations, and meter accuracy. The results indicate that high pressure during minimum demand hours significantly contributes to physical leakage. Proposed mitigation strategies include the implementation of step-test, installation of Pressure Reducing Valves (PRVs), calibration of district inlet meter, and the application of an IoT-based SCADA system for real-time monitoring. The integration of these technologies is expected to enhance operational efficiency and extend the lifespan of the water distribution network.